Transplacental Transfer of Iron in the Water Buffalo (Bubalus bubalis): Uteroferrin and Erythrophagocytosis - Pereira, F. T. V. [UNESP]; Braga, F. C.; Burioli, K. C. [UNESP]; Kfoury, J. R.; Oliveira, L. J.; Papa, P. C.; Carvalho, A. F.; Ambrosio, C. E.; Bazer, F. W.; Miglino, M. A. (Wiley-Blackwell Publishing, Inc, 2010)
The objectives of this investigation were to understand transplacental transport of iron by secreted uteroferrin (UF) and haemophagous areas of water buffalo placenta and clarify the role(s) of blood extravasation at the placental-maternal interface. Placentomes and interplacentomal region of 51 placentae at various stages of gestation were fixed, processed for light and transmission electron microscopy, histochemistry and immunohistochemistry. Haemophagous areas were present in placentomes collected between 4 and 10 months of pregnancy. Perl's reaction for ferric iron was negative in placentomes, but positive in endometrial glands. Positive staining for UF indicated areas in which it was being taken up by phagocytosis and/or fluid phase pinocytosis in areolae of the interplacentomal mesenchyme, with little staining in endometrial stroma. Imunohistochemistry detected UF in trophectoderm of haemophagous regions of placentomes and in other parts of the foetal villous tree, but the strongest immunostaining was in the epithelial cells and lumen of uterine glands. Ultrastructural analyses indicated that erythrophagocytosis was occurring and that erythrocytes were present inside cells of the chorion that also contained endocytic vesicles and caveolae. Results of this study indicate that both the haemophagous areas of placentomes and the areolae at the interface between chorion and endometrial glands are important sites for iron transfer from mother to foetal-placental tissues in buffalo throughout pregnancy.